1983
DOI: 10.1159/000183068
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Aluminium on the Effect of 1α (OH) D<sub>3</sub> on Renal Osteodystrophy

Abstract: The influence of aluminium in dialysate on the effects of 1α(OH)3 on hemodialyzed hypocalcemic patients with end-stage renal failure, was studied during a 24- to 42-month period. 51 hypocalcemic patients were divided into two groups; group 1 consisted of 28 patients who were dialyzed using dialysate prepared from reverse osmosed water; the 23 patients in group 2 used dialysate prepared from softened water. Aluminium concentration in the dialysate used for group 1 was less than the detectable limit (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 20 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Thus, la-O H D , treatment maintained relatively high plasma concentrations of aluminium (2.6±0.7 um ol/l), concentrations which are not usually associated with overt encephalopathy or osteomalacia but which may interfere with bone remodelling since Shimada et al [26] have shown that la-OH D, was more effective in curing subperiosteal resorption in patients with a plasma alumi nium of 1.7 [i.mol/1 than in patients with a plasma alumi nium of 3.1 pm ol/l, the differences of plasma aluminium in this study being explained by the concentration of aluminium in the dialysate. It is interesting to note that the plasma concentrations of aluminium of their group treated with low aluminium dialysate were however sign ificantly higher than in our patients treated with high calcium carbonate alone, the reason being that they were receiving la-O H D , and Al(OH),.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, la-O H D , treatment maintained relatively high plasma concentrations of aluminium (2.6±0.7 um ol/l), concentrations which are not usually associated with overt encephalopathy or osteomalacia but which may interfere with bone remodelling since Shimada et al [26] have shown that la-OH D, was more effective in curing subperiosteal resorption in patients with a plasma alumi nium of 1.7 [i.mol/1 than in patients with a plasma alumi nium of 3.1 pm ol/l, the differences of plasma aluminium in this study being explained by the concentration of aluminium in the dialysate. It is interesting to note that the plasma concentrations of aluminium of their group treated with low aluminium dialysate were however sign ificantly higher than in our patients treated with high calcium carbonate alone, the reason being that they were receiving la-O H D , and Al(OH),.…”
Section: Discussionmentioning
confidence: 93%